TIM-3 Dictates Functional Orientation of the Immune Infiltrate in Ovarian Cancer - Fucikova, Jitka; Rakova, Jana; Hensler, Michal; Kasikova, Lenka; Belicova, Lucie; Hladikova, Kamila; Truxova, Iva; Skapa, Petr; Laco, Jan; Pecen, Ladislav; Praznovec, Ivan; Halaska, Michael J; et al. (Clinical cancer research, 2019)
PURPOSE: In multiple oncological settings, expression of the coinhibitory ligand PD-L1 by malignant cells and tumor infiltration by immune cells expressing coinhibitory receptors such as PD-1, CTLA4, LAG-3, or TIM-3 conveys prognostic or predictive information. Conversely, the impact of these features of the tumor microenvironment on disease outcome among high-grade serous carcinoma (HGSC) patients remains controversial. EXPERIMENTAL DESIGN: We harnessed a retrospective cohort of 80 chemotherapy-naïve HGSC patients to investigate PD-L1 expression and tumor infiltration by CD8+ T cells, CD20+ B cells, DC-LAMP+ dendritic cells as well as by PD-1+, CTLA4+, LAG-3+, and TIM-3+ cells in relation with prognosis and function orientation of the tumor microenvironment. IHC data were complemented with transcriptomic and functional studies on a second prospective cohort of freshly resected HGSC samples. In silico analysis of publicly available RNA expression data from 308 HGSC samples was used as a confirmatory approach. RESULTS: High levels of PD-L1 and high densities of PD-1+ cells in the microenvironment of HGSCs were strongly associated with an immune contexture characterized by a robust TH1 polarization and cytotoxic orientation that enabled superior clinical benefits. Moreover, PD-1+TIM-3+CD8+ T cells presented all features of functional exhaustion and correlated with poor disease outcome. However, although PD-L1 levels and tumor infiltration by TIM-3+ cells improved patient stratification based on the intratumoral abundance of CD8+ T cells, the amount of PD-1+ cells failed to do so. CONCLUSIONS: Our data indicate that PD-L1 and TIM-3 constitute prognostically relevant biomarkers of active and suppressed immune responses against HGSC, respectively.
Keywords: regulace genové exprese u nádorů; dospělí; Carcinoma, Ovarian Epithelial; tumor infiltrující lymfocyty; Female; Adult; ženské pohlaví; Gene Expression Regulation, Neoplastic; Lymphocytes, Tumor-Infiltrating; buněčný receptor 2 viru hepatitidy A; B7-H1 Antigen; antigen CTLA-4; CTLA-4 Antigen; lidé; CD8-Positive T-Lymphocytes; epiteliální ovariální karcinom; serózní cystadenokarcinom; míra přežití; prognóza; Lysosomal Membrane Proteins; retrospektivní studie; CD8-pozitivní T-lymfocyty; nádorové biomarkery; Aged; membránové glykoproteiny asociované s lyzozomy; nádorové proteiny; Neoplasm Proteins; Prognosis; Survival Rate; Hepatitis A Virus Cellular Receptor 2; antigeny CD274; lidé středního věku; Biomarkers, Tumor; senioři; Cystadenocarcinoma, Serous; Retrospective Studies; Middle Aged; Humans